Pengaruh Dividend Payout Ratio, Price to Book Value Ratio, dan Price to Earnings Ratio pada Return Saham di Bursa Efek Indonesia Periode 2009-2011 - Januari Antara, I Made (E-Jurnal Akuntansi; Vol 1 No 1 (2012), 2012)
This study aims to determine the effect of dividend payout ratio, price to book value ratio, and  price to earnings ratio on stock returns in IDX and using secondary data from company financial statements of LQ45 during 2009-2011 period. Sampling method used is purposive sampling. The analysis show that only DPR does not have effect on the stock returns, while PBV and PER negatively affect stock return Keyword: Dividend Payout Ratio, Price to Book Value Ratio, Price to Earnings Ratio, Stock Return